Intensity dynamics in a waveguide array laser - Feng, Mingming; Williams, Matthew O.; Kutz, J. Nathan; Silverman, Kevin L.; Mirin, Richard P.; Cundiff, Steven T. (Optics communications, 2011)
We consider experimentally and theoretically the optical field dynamics of a five-emitter laser array subject to a ramped injection current. We have achieved experimentally an array that produces a robust oscillatory power output with a nearly constant π phase shift between the oscillations from each waveguide. The output power also decreases linearly as a function of waveguide number. Those behaviors persisted for pump currents varying between 380 and 500 mA with only a slight change in phase. Of note is the fact that the fundamental frequency of oscillation increases with injection current, and higher harmonics are produced above a threshold current of approximately 380 mA. Experimental observations and theoretical predictions are in agreement. A low dimensional model was also developed and the impact of the nonuniform injection current studied. A nonuniform injection current is capable of shifting the bifurcations of the waveguide array providing a valuable method of array tuning without additional gain or structural alterations to the array. ►Five-emitter array fabricated with a sloped injection current. ►Array produces oscillatory power output between 380 and 500 mA. ►Frequency of power oscillation is directly related to injection current. ►Good agreement between experiment and the theoretical model. ►Injection current slope alters the gain at where the array loses stability.